Carbon neutrality-oriented green resilience and low-carbon innovation in Macau: a multi-criteria assessment framework for sustainable regional development - Lin, Shuaijun; Zhang, Hongfeng (Frontiers in Environmental Science, 2025)
Global climate change and international carbon neutrality commitments create unprecedented pressures for sustainable transformation. China’s dual carbon goals and Green Quality Productive Forces development strategy require coordinated regional implementation, particularly challenging for gaming-dependent small economies. This study focuses on Macau as a representative case to investigate environmental-economic resilience and green collaborative innovation capabilities under carbon neutrality constraints. The research objectives encompass developing a comprehensive evaluation framework for small economies’ carbon-neutral development, identifying critical transformation factors, and formulating regional green innovation integration strategies. A multi-criteria decision analysis framework integrating AHP, BWM, and DEMATEL methodologies was employed through systematic literature review and expert consultation using Delphi method. Initial weights were determined through AHP pairwise comparisons with consistency verification, while BWM provided robustness validation and DEMATEL quantified inter-factor relationships. Results reveal long-term green development resilience significantly outweighs short-term environmental-economic resilience (0.42312 vs. 0.12252). Green industrial diversification emerges as the most critical factor (0.107), followed by carbon neutrality capacity (0.072) and regional integration coordination (0.071). Methodological triangulation demonstrates stability with correlation coefficients exceeding 0.85. These findings provide theoretical insights into small economy carbon-neutral pathways and practical frameworks for gaming-dependent jurisdictions, demonstrating that structural transformation and strategic regional positioning constitute more effective approaches than conventional policy interventions.